2022
DOI: 10.1371/journal.pone.0274844
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neurobehavioral pattern in a zebrafish 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced model: A 96-hour behavioral study

Abstract: Parkinson’s disease (PD) is the most common brain motor disorder, characterized by a substantial loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). Motor impairments, such as dyskinesia, bradykinesia, and resting tremors, are the hallmarks of PD. Despite ongoing research, the exact PD pathogenesis remains elusive due to the disease intricacy and difficulty in conducting human studies. Zebrafish (Danio rerio) has emerged as an ideal model for researching PD pathophysiology. Even though 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Following intraperitoneal administration of a single dose of MPTP (100 μg/g bw per fish), fish exhibited impairments in motor function as demonstrated by significant reductions in mean speed and total distance traveled. Similarly, previous studies using intraperitoneal injections of 200 μg/g bw, and intracranial injection of 25 mM MPTP in adult zebrafish also demonstrated reduced locomotor activity ( Kalyn and Ekker, 2021 ; Razali et al, 2022 ).…”
Section: Discussionsupporting
confidence: 72%
“…Following intraperitoneal administration of a single dose of MPTP (100 μg/g bw per fish), fish exhibited impairments in motor function as demonstrated by significant reductions in mean speed and total distance traveled. Similarly, previous studies using intraperitoneal injections of 200 μg/g bw, and intracranial injection of 25 mM MPTP in adult zebrafish also demonstrated reduced locomotor activity ( Kalyn and Ekker, 2021 ; Razali et al, 2022 ).…”
Section: Discussionsupporting
confidence: 72%
“…At the end of the study, OT-treated fish showed a decreased level of meandering, which suggests that hormone exposure had no a negative impact. A larger meander is linked with erratic movements, according to several studies where a neurotoxic impact was seen in zebrafish swimming patterns [ 72 , 73 ]. In humans, improvements in social and repetitive behaviors were observed after the administration of 24 IU OT once a day for four days and twice a day for six weeks [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of producing α-synuclein, zebrafish produce homologues that behave differently, namely β-synuclein (SNCB) and gamma b synuclein (SNCG1). Β-synuclein is believed to have a protective role against α-synuclein aggregation in humans 41 while gamma b synuclein has been suggested to behave similarly to human α-synuclein 42 . Both related genes were statistically downregulated in our study, which has been linked to decreased motor activity and neural DA levels in other zebrafish studies 43,44 .…”
Section: Discussionmentioning
confidence: 99%